Analysis of buñuelos growth rate using 2K factorial design (2020)
Buñuelos are a traditional food not only in Colombia but in several parts of the world. They are prepared mainly with cassava starch, cornstarch, cheese, water or milk. The purpose of this work is to determine which factors (trademark, time, temperature, serving size) or interactions between them are important to achieve a major volume of the buñuelos. Thus, a 2k design is proposed to analyze the factors on the growth rate of buñuelos. The growth rate is calculated taking into account the buñuelos diameter before fried and after fried. The results indicate that the serving size has the principal effect on the response variable but followed by the trademark and some interactions between time and temperature.